High-flame-retardant self-reinforced halogen-free flame-retardant PA66 material and preparation method thereof
By adding LCP to PA66 material and using secondary processing technology, the problems of unstable and insufficient rigidity are solved, high flame retardant performance and self-reinforcement effect are achieved, ensuring the V0-level flame retardant and high pulling of the material Extension strength.
Patent Information
- Application Number
- CN202411638450.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-17
- Publication Date
- 2025-01-07
AI Technical Summary
The flame retardant of PA66 halogen-free and reinforced flame retardant materials is unstable, and it is prone to dripping and ignition that cannot reach V0 level. The material has low rigidity and a large linear expansion coefficient.
By adding a small amount of LCP, the melt viscosity is reduced, the dripping droplets during combustion are reduced, and the extinguishing of the droplet flame is accelerated; secondary processing is adopted, and the slender die holes are high shear stretched after the first high temperature melting, so that the LCP is fully oriented in flame retardant and synergistic masterbatch, and the LCP morphology is retained during the second melt blending, playing a self-enhancement role.
The high flame retardant performance of the material is achieved stably reaching V0 level, improving the tensile strength and impact strength, and ensuring the self-reinforcement effect of the material.
Abstract
Description
Technical Field
[0001] The invention relates to a modified nylon technology, and in particular to a highly flame-retardant, self-reinforced halogen-free flame-retardant PA66 material and a preparation method thereof. Background Art
[0002] When PA66 material is used to prepare non-reinforced flame retardant materials with halogen-free nitrogen flame retardants, the following problems will occur: 1: This material produces inert gas through MCA high-temperature decomposition, thereby diluting the combustible gas and producing molten droplets, which reduces the temperature at the combustion point, so that the combustion product is extinguished quickly. However, the molten droplets are often large and have flames. The flames cannot be extinguished in time during the dripping process of the molten droplets, causing the absorbent cotton to burn, and thus failing to reach the V0 level. In particular, the flame retardancy of this formula system is very unstable, and trace amounts of pigments and additives may cause the flame retardancy to become V2 level; 2: Since the material has no filling or reinforcing components, the rigidity of the material is low and the linear expansion coefficient is large. Therefore, it is of great value and significance to develop a PA66 halogen-free flame retardant material with stable flame retardancy reaching V0 level and improved strength.
[0003] Regarding the patents related to PA66 halogen-free and non-reinforced flame retardant, patent CN 115418102 B 2 discloses a halogen-free flame retardant PA66 material with high GWIT and high CTI and its preparation method, which involves compounding modified vermiculite with expandable graphite to form expandable graphite / modified vermiculite as a flame retardant to improve the flame retardancy and mechanical properties of the PA66 material, while reducing the effect of the flame retardant on CTI, so that the product has both high GWIT and high CTI.
[0004] The Chinese patent with publication number CN104119676A discloses a halogen-free flame retardant for PA66 and an environmentally friendly flame-retardant PA66 material prepared therefrom. The halogen-free flame retardant is used and sodium bicarbonate is added. Carbon dioxide gas can be decomposed in the PA66 material under high temperature conditions and expand to form a small air chamber; the air chamber can store carbon dioxide gas and nitrogen until the air chamber is ruptured by combustion, and the gas is released to inhibit the combustion; this can prevent nitrogen from being released too quickly, resulting in a decrease in the flame retardant properties of the PA66 material; because melamine cyanurate can be stored in the air chamber without escaping, the amount of melamine cyanurate added to the PA66 material can be reduced, thereby reducing production costs.
[0005] Patent publication number CN114806164A discloses a halogen-free flame retardant PA66 and its preparation method, including the following raw materials: 7585 parts of PA66; 815 parts of melamine cyanurate; 5-10 parts of thermoplastic nylon elastomer; 0.52 parts of polytetrafluoroethylene; 0.1-0.3 parts of maleic anhydride; 0.2-0.5 parts of antioxidant; 0.3-0.5 parts of lubricant. The amide group in the thermoplastic nylon elastomer of the present invention has very good compatibility with nylon, and has a better toughness modification effect when added to the nylon formula system; at the same time, the thermoplastic nylon elastomer has nylon blocks as rigid segments, which can slow down the strength decline of the nylon toughening system, that is, it will not reduce the rigidity; and due to the presence of nylon blocks, the melting point of the thermoplastic nylon elastomer can reach about 200 degrees Celsius, so the risk of dripping ignition can be reduced.
[0006] Patent No. CN113845771A discloses a halogen-free flame-retardant PA66 composite material and its preparation method. The dried 80-92% PA66 resin, 6-15% melamine cyanurate, 0.2-5% graphene, and 0.2-5% multi-walled carbon nanotubes are stirred and mixed evenly at high speed, extruded, pelletized, and finally packaged to obtain halogen-free flame-retardant PA66. In the present invention, graphene and multi-walled carbon nanotubes can effectively prevent the overflow of flammable or toxic gases formed by polymer decomposition and the entry of external heat and oxygen, and have excellent carbonization and excellent flame retardant effect. At the same time, the reinforcement effect of carbon-based nanofillers improves the mechanical properties; the halogen-free flame-retardant PA66 composite material not only has high flame retardant efficiency, halogen-free, low smoke, low toxicity, and anti-dripping, but also has excellent processing performance and can be widely used; the preparation method of the halogen-free flame-retardant PA66 material of the present invention has the advantage of simple operation.
[0007] Patent publication number CN103242655B discloses a halogen-free flame-retardant PA66 plastic modified material and a preparation method thereof, which is composed of the following raw materials in parts by weight: 87-92 parts of PA66 resin, 8-12 parts of halogen-free flame retardant, 0.2-0.5 parts of nucleating agent, 0.2-0.5 parts of lubricant, 0.2-0.5 parts of zinc stearate, 0.2-0.4 parts of antioxidant, and 0.1-0.2 parts of methyl silicone oil; this invention not only has good flame retardant properties, the flame retardant properties can reach UL94V0 level, but also has excellent tensile strength, bending strength and other mechanical properties, long service life, and the electronic connector prepared by using the same has strong flame retardant properties and high safety; the present invention does not contain halogen, is environmentally friendly, can produce great environmental protection benefits, and can meet the environmental protection requirements of most countries or regions. The preparation method of the present invention is simple to operate, requires less equipment, and has low production cost. Summary of the invention
[0008] The invention relates to a halogen-free flame retardant technology for nylon materials. By adding a small amount of LCP, the melt viscosity is reduced by taking advantage of the self-extinguishing performance, low melt strength and high rigidity of LCP, so that the molten droplets dripping during combustion become smaller and the extinguishing of the molten droplet flame is accelerated. Secondly, due to the adoption of secondary processing, the first high-temperature melting and the high-shear stretching of the melt through a slender die hole make the LCP fully oriented in the flame retardant synergistic masterbatch. During the second melt blending, since the processing temperature is lower than the melting temperature of the LCP, the LCP morphology is retained, which plays a good reinforcing role and achieves the self-reinforcement effect of the material.
[0009] The present invention solves the problem that the flame retardant of PA66 halogen-free unreinforced nitrogen-based materials is unstable and prone to dripping and ignition and cannot reach the V0 level; due to the addition of a small amount of LCP, the melt viscosity is reduced, so that the dripping droplets during combustion become smaller, and the LCP has a good self-extinguishing effect. If there is a small amount of flame in the droplet, the flame can be quickly extinguished, thereby not igniting the absorbent cotton; secondly, due to the use of secondary processing, the first high-temperature melting and the melt being stretched through a slender die hole make the LCP fully oriented in the flame retardant and synergistic masterbatch. During the second melt blending, since the processing temperature is lower than the LCP melting temperature, the LCP morphology is retained, which plays a good reinforcing role and greatly improves the tensile strength of the material.
[0010] The present invention is a highly flame-retardant, self-reinforced halogen-free flame-retardant PA66 material realized by the following technical scheme, comprising the following raw materials in percentage by weight: Polyamide (PA66) 53~86.5%; MCA 8-15.0%; Enhanced flame retardant synergist 5~30.0%; Heat stabilizing agent 0.3~1.0%; Lubricant 0.2~1.0%.
[0011] The PA66 is PA66 slices with different viscosities, and generally the intrinsic viscosity is controlled between 2.3 and 2.7.
[0012] The MCA is one or more of different particle sizes, different microstructures (sheet-shaped, rod-shaped), and has undergone special surface treatment.
[0013] The enhanced flame retardant synergist is a PA66 masterbatch with an LCP content of 5-20%, preferably an LCP content of 10%, wherein the LCP is one or more of Celanese, Polyplastics, and Toray.
[0014] The heat stabilizer is an antioxidant, which can be one or more of N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (antioxidant 1098), tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168), tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester (antioxidant 1010), and bis(2,4-dicumylphenyl)pentaerythritol diphosphite (antioxidant 9228).
[0015] The lubricant is one or more of calcium stearate, modified ethylene bis fatty acid amide (TAF), and ethylene-acrylic acid copolymer.
[0016] The method for preparing a highly flame-retardant, self-reinforced halogen-free flame-retardant PA66 material comprises step one and step two; Step 1: Evenly mix PA66, LCP, heat stabilizer, etc., add the main feed into the twin-screw extruder, use a high-speed twin-screw extruder, use a special die plate, mix through a high-shear, high-dispersion screw combination, extrude, draw, cool, pelletize and dry to obtain PA66 flame retardant synergistic masterbatch; the aspect ratio of the twin-screw extruder is 36~44:1.
[0017] The temperature of each working section in the twin-screw extruder is 275°C~350°C, and the specific settings of each zone of the twin-screw extruder are preferably: 285°C~315°C~330°C~330°C~320°C~320°C~320°C~320°C~305°C~300°C, the die head temperature is 310°C; the main engine speed is 500~1000rpm / min, preferably 800rpm / min; special die plate: die plate thickness is 8~15cm, die hole diameter is 0.8~1.5mm; preferably: die plate thickness is 10cm, die hole diameter is 1mm (so that LCP is fully oriented under high shear conditions when passing through the die plate).
[0018] Step 2: Evenly mix PA66, MCA, PA66 flame retardant synergist masterbatch, lubricant, etc., add the main feed into the twin-screw extruder, and obtain a highly flame retardant, self-reinforced halogen-free flame retardant PA66 material after extrusion, drawing, cooling, pelletizing and drying; The aspect ratio of the twin-screw extruder is 36-44:1; the temperature of each working section in the twin-screw extruder is 210°C-300°C, and the specific settings of each zone of the twin-screw extruder are preferably: 255°C-275°C-270°C-270°C-260°C-250°C-250°C-245°C-235°C-220°C, the die head temperature is 265°C, and the main engine speed is 300-600rpm / min; a common mouth template is used, the template thickness is 2.5-4.0cm, and the die hole diameter is 3.5-4.5mm. DETAILED DESCRIPTION
[0019] The present invention will be further described below in conjunction with Comparative Examples 1-2 and Examples 1-5.
[0020] First, PA66 2.4 viscosity substrate and LCP were selected according to step 1 to make a flame retardant and enhanced masterbatch with an LCP content of 10%. LCP is a product of Celanese. The temperature of each working section in the twin-screw extruder is: 285~315~330~330~320~320~320~320~320℃~305℃~300, the die head temperature is 310℃, and the main engine speed is 800rpm / min.
[0021] Special die plate: die plate thickness 10cm, die hole diameter 1mm (so that LCP can be fully oriented under high shear conditions when passing through the die plate); then weigh the raw materials according to the ratio in Table 1, mix PA66, flame retardant and synergistic masterbatch, stabilizer and lubricant evenly, add the main feed into the twin-screw extruder, mix through a high-shear, high-dispersion screw combination, extrude, draw, cool, pelletize and dry, and obtain a highly flame-retardant self-reinforced halogen-free flame-retardant PA66 material.
[0022] In step 2, the temperature of each working section of the twin-screw extruder is 255°C~275°C~270°C~270°C~260°C~250°C~250°C~245°C~235°C~220°C, the die head temperature is 265°C, the main engine speed is 300~600rpm / min, the common mouth template template thickness is 2.5~4.0cm, and the die hole diameter is 3.5~4.5mm.
[0023] Compare the flame retardant properties, tensile strength and impact strength of the prepared materials Table 1. Specific ratios of Comparative Examples 1 to 2 and Examples 1 to 5 formula Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Example 4 Example 5 PA66 89 84 84 79 69 59 49 MCA 10 15 10 10 10 10 10 Enhanced flame retardant synergist 0 0 5 10 20 30 40 Lubricants 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Heat Stabilizer 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Table 2. Performance analysis results of Comparative Examples 1-2 and Examples 1-5 Sample name Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Example 4 Example 5 Is it dripping? Dripping (large molten drop) Dripping (large molten drop) Dripping (small droplets) Dripping (small droplets) Dripping (small droplets) Dripping (small droplets) Dripping (small droplets) Flame retardant performance (0.8mm) V2 V2 V0 V0 V0 V0 V0 Tensile strength (MPa) 70 68 76 82 86 90 95 <![CDATA[Notched impact strength (kJ / m 2 ).]]> 5.5 5.2 5.5 5.4 5.3 5 3.2 It is found from the data in Table 2 that the comparison 1 and comparison 2 show that the addition of flame retardant does not significantly improve the flame retardant performance, but the tensile strength and impact performance of the material are reduced to a certain extent; it is found from comparative example 1 and example 1 that when 5% of the homemade enhanced flame retardant synergist is added to the material (LCP content reaches 0.5%), the flame retardant performance can stably reach the V0 level, and the tensile strength is significantly improved; with the increase of homemade enhanced flame retardant synergist (LCP content continues to increase), the flame retardant performance stably reaches the V0 level, the tensile strength continues to increase, but the impact strength is constantly decreasing. When the enhanced flame retardant synergist reaches 50% (the actual amount of LCP added reaches 5%), it is found that the impact strength of the material has decreased by 42%. Therefore, under normal circumstances, the amount of LCP added is not recommended to exceed 5%. Therefore, it can be found that this invention can significantly improve the flame retardant performance of the material, and the tensile strength is significantly improved when the LCP content is within 3%, and the impact strength can also ensure good performance.
[0024] To further illustrate the present invention, Examples 6 to 10 used LCP from different manufacturers, as well as different die plates and process parameters.
[0025] Compared with Example 1, Example 6 uses LCP from Toray; other conditions are the same as Examples 1 to 5.
[0026] Compared with Example 1, Example 7 has a template thickness of 8 cm and a mold hole diameter of 0.8 mm; other conditions are the same as Examples 1 to 5.
[0027] Compared with Example 1, Example 8 has a template thickness of 12 cm and a mold hole diameter of 1.3 mm; other conditions are the same as Examples 1 to 5.
[0028] Compared with Example 1, in Example 9, the temperature of each working section and the die head temperature in the twin-screw extruder in step 2 are increased by 10° C. compared with Example 1, and other conditions are the same as in Examples 1-5.
[0029] Compared with Example 1, in Example 10, the temperature of each working section in the twin-screw extruder and the die head temperature in step 2 are reduced by 10°C compared with Example 1 (the temperature is assumed to be lower than the melting point of PA66, but in fact the melt temperature in the twin-screw extruder is about 20°C higher, and there is no problem of PA66 not melting), and other conditions are the same as in Examples 1 to 5.
[0030] Table 3 Specific ratios of Examples 6 to 10 formula Example 6 Example 7 Example 8 Example 9 Example 10 PA66 84 84 84 84 84 MCA 10 10 10 10 10 Enhanced flame retardant synergist 5 5 5 5 5 Lubricants 0.5 0.5 0.5 0.5 0.5 Heat Stabilizer 0.5 0.5 0.5 0.5 0.5 Table 4 Performance analysis results of Examples 6 to 10 Sample name Example 6 Example 7 Example 8 Example 9 Example 10 Is it dripping? Dripping (small droplets) Dripping (small droplets) Dripping (small droplets) Dripping (small droplets) Dripping (small droplets) Flame retardant performance (0.8mm) V0 V0 V0 V0 V0 Tensile strength (MPa) 78 83 69 68 75 <![CDATA[Notched impact strength (kJ / m 2 ).]]> 5.6 5.7 5.3 5.2 4.9 From the data in Table 4, it can be found that the performance of Example 6 is better than that of Example 1, and the LCP produced by Toray has better performance in this formulation system. Although the performance of Example 7 is relatively good, due to the use of a template with a thickness of 8 cm and a die hole diameter of 0.8 mm, it is difficult to draw the strip during the molding process, the strip is easily broken, and the material consumption is large. Example 8 uses a template with a thickness of 12 cm and a die hole diameter of 1.3 mm. The orientation of LCP is worse than that of Example 1, and the resulting tensile and impact are low. Examples 9 to 10 show that in step 2, the temperature is too low, and the impact is worse than that of Example 1. After the temperature is set high, the tensile and impact are reduced at the same time compared with Example 1.
Claims
1. A highly flame retardant, self-reinforced halogen-free flame retardant PA66 material, characterized in that: Contains the following raw materials in weight percentage: Polyamide (PA66) 53~86.5%; MCA 8-15.0%; Enhanced flame retardant synergist 5~30.0%; Heat stabilizing agent 0.3~1.0%; Lubricant 0.2~1.0%.
2. The highly flame-retardant, self-reinforced halogen-free flame-retardant PA66 material according to claim 1, characterized in that: The PA66 is PA66 slices with different viscosities, and generally the intrinsic viscosity is controlled between 2.3 and 2.
7.
3. The highly flame-retardant, self-reinforced halogen-free flame-retardant PA66 material according to claim 1 is characterized in that: The MCA is one or more of different particle sizes, different microstructures (sheet-shaped, rod-shaped), and has undergone special surface treatment.
4. The highly flame-retardant, self-reinforced halogen-free flame-retardant PA66 material according to claim 1 is characterized in that: The enhanced flame retardant synergist is a PA66 masterbatch with an LCP content of 5-20%, wherein the LCP is one or more of Celanese, Polyplastics, and Toray.
5. The highly flame-retardant, self-reinforced halogen-free flame-retardant PA66 material according to claim 1 is characterized in that: The heat stabilizer is an antioxidant, which can be one or more of N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (antioxidant 1098), tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168), tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester (antioxidant 1010), and bis(2,4-dicumylphenyl)pentaerythritol diphosphite (antioxidant 9228).
6. The highly flame-retardant, self-reinforced halogen-free flame-retardant PA66 material according to claim 1, characterized in that: The lubricant is one or more of calcium stearate, modified ethylene bis fatty acid amide (TAF), and ethylene-acrylic acid copolymer.
7. The method for preparing a highly flame-retardant, self-reinforced halogen-free flame-retardant PA66 material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: uniformly mixing PA66, LCP, a heat stabilizer, etc., adding the main feed into a twin-screw extruder, using a high-speed twin-screw extruder and a special die plate, mixing through a high-shear, high-dispersion screw combination, extruding, drawing, cooling, pelletizing and drying, to obtain a flame retardant synergist; In step 1, the aspect ratio of the twin-screw extruder is 36-44:1; the temperature of each working section of the twin-screw extruder is 275°C-350°C, the main engine speed is 500-1000rpm / min; the special die plate has a die thickness of 8-15cm and a die hole diameter of 0.8-1.5mm; Step 2: Evenly mix PA66, MCA, enhanced flame retardant synergist, lubricant, etc., add the main feed into a twin-screw extruder, and obtain a highly flame-retardant self-reinforced halogen-free flame-retardant PA66 material after extrusion, drawing, cooling, pelletizing and drying; the aspect ratio of the twin-screw extruder is 36-44:1; the temperature of each working section in the twin-screw extruder is 210°C-300°C; a common die plate is used, the die plate thickness is 2.5-4.0cm, and the die hole diameter is 3.5-4.5mm.
Citation Information
Patent Citations
Halogen-free flame-retardant PA66 plastic modified materials and their preparation methods
CN103242655B
Halogen-free flame retardant for PA66 and environment-friendly flame-retardant PA66 material prepared thereby
CN104119676A
Halogen-free flame-retardant PA66 composite material and preparation method thereof
CN113845771A
Halogen-free flame-retardant PA66 and preparation method thereof
CN114806164A
Flame-retardant engineering plastic and method for preparing same
CN106046773A